The Evaluative Research of Complex Projects in e-Learning: The Case of the ‘EQUEL’ (e-Quality in e-Learning) Project - Bonamy, Joel; Charlier, Bernadette; Saunders, Murray (Proceedings of the International Conference on Networked Learning, 2004)
This paper addresses the evaluative research of complex European projects aimed at social, educational or training development. It proposes a social practice approach that emphasises the way a project [in this case EQUEL] evolves over time and is expressed through the experience of its key stakeholders. The paper identifies the metaphor of the implementation staircase as a useful framework for this approach. Its theoretical stance is that a project idea is modified and adapted in the light of the strategic, practice based concerns of each stake-holding group occupying a ‘step’ in the staircase. It suggests that EQUEL has the potential to be a rich resource for e-learning within the Union.